Analisis Penggunaan Metode Altman Z-Score Dalam Memrediksi Financial Distress Pada Perusahaan Manufaktur Sub Sektor Otomotif Dan Komponen Yang Terdaftar di BEI Tahun 2018-2020 - Palahiah; Nurabiah (Jurnal Riset Mahasiswa Akuntansi, 2025)
The purpose of this study is to determine the level of financial distress in automotive and component sub-sector manufacturing companies listed on the IDX in 2018-2020 using the Altman Z-Score model. The type of research used in this study is quantitative descriptive research. Sampling in this study used the purposive sampling method, which is a method carried out by collecting population data based on certain criteria. The total sample was 24 observers. The results of the study showed that of the eight companies analyzed, there were two companies in financial distress, four companies in the safe zone category, while the other two companies were in the gray area. The Covid-19 pandemic that occurred in 2020 had a significant impact on the eight companies, this affected the company in obtaining profits and resulted in a decrease in the Z-Score value of the eight companies, which means that the financial performance in that year decreased from the previous year.